1996
DOI: 10.1038/bjc.1996.276
|View full text |Cite
|
Sign up to set email alerts
|

Randomised multicentre trials of CHART vs conventional radiotherapy in head and neck and non-small-cell lung cancer: an interim report. CHART Steering Committee

Abstract: Summary While radiotherapy is proceeding. tumour cells may proliferate. The use of small individual doses reduces late morbidity. Continuous hy-perfractionated accelerated radiation therapy (CHART). which reduces overall treatment from 6-7 weeks to 12 days and gives 36 small fractions. has now been tested in multicentre randomised controlled clinical trials. The trial in non-small-cell lung cancer included 563 patients and showed improvement in survival: 30% of the CHART patients were alive at 2 years compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(41 citation statements)
references
References 15 publications
0
39
0
2
Order By: Relevance
“…In this study, there was a trend for improved local control of advanced tumours, particularly laryngeal cancer (Saunders et al, 1996). Acute skin reactions were less than with conventional regimens, as was late treatment-related morbidity.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…In this study, there was a trend for improved local control of advanced tumours, particularly laryngeal cancer (Saunders et al, 1996). Acute skin reactions were less than with conventional regimens, as was late treatment-related morbidity.…”
Section: Resultsmentioning
confidence: 64%
“…The problem is particularly associated with accelerated hyperfractionated regimens. Mucosal reactions tend to peak earlier and are more severe but are of shorter duration than those after conventional treatment (Saunders et al, 1996). As these regimens are associated with improved local control, particularly in advanced disease (Horiot et al, 1997), any effective measure that can reduce this side-effect will be very useful to patients treated by twice or three times daily radiation regimens.…”
mentioning
confidence: 99%
“…The use of altered fractionation radiotherapy (AFRT) for treatment of oropharyngeal cancer has demonstrated superiority in locoregional control and long-term survival when compared with conventionally fractionated radiotherapy [1][2][3] . AFRT with concomitant boost (AFRT-CB) delivers radiotherapy in an accelerated format without total dose reduction, resulting in heightened toxicity which may persist longer and result in a higher incidence of severe functional injury, including possible deleterious effects on swallowing and nutrition [4][5][6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Some statisticians and clinical triallists would prefer an approach to interim analyses that is more flexible and pragmatic to the stopping rules used in the Herskovic trial, formally and informally taking into account the degree of 'scepticism' prevalent at the time of a trial. A so-called Bayesian approach to monitoring trials (Parmar et (Saunders et al, 1996, one of the main conclusions was that overall treatment time was shown to be important with respect to survival in the management of squamous carcinomas of the bronchus . Perhaps future investigational therapy should involve a shorter overall treatment time for carcinoma of the oesophagus and indeed CHART for oesophageal carcinoma is currently being investigated (Powell et al, 1997).…”
Section: Is Radiation-chemotherapy Now Standard Treatment For the Radmentioning
confidence: 99%